Synthesis of Halogen-Bond-Donor-Site-Introduced Functional Monomers through Wittig Reaction of Perfluorohalogenated Benzaldehydes: Toward Digitalization as Reliable Strategy in Small-Molecule Synthesis - Hori, Tatsuaki; Kakinuma, Shuya; Ohtsuka, Naoya; Fujinami, Takeshi; Suzuki, Toshiyasu; Momiyama, Norie (Synlett, 2023)
The Wittig reaction of perfluoromonohalobenzaldehydes was systematically studied to synthesize 2,3,5,6-tetrafluoro-4-halostyrene (TFXSs) as functional monomers bearing halogen-bond donor sites. The reaction proceeded efficiently in tetrahydrofuran using 1,1,3,3-tetramethylguanidine as an organic base. Correlation analysis quantitatively identified three key factors required to obtain TFXSs in reasonable yields. The present approach not only contributes to the study of halogen-bond-based functional molecules, but also presents digitalization as a potential strategy in small-molecule synthesis.
Keywords: perfluorohalo styrenes; halogen bond; functional monomers; digitalization of organic synthesis; Wittig reaction